Pengamalan Thariqoh Qodiriyah Wa Naqsabandiyah Sebagai Pendidikan Akhlak Di Pondok Pesantren Miftahul Huda Malang - Damanhuri, Damanhuri; Habibi, M. Dani (JURNAL JAWI, 2021)
The development of Islam, especially in the field of Sufism, continues to progress, both in terms of empowering thoughts and ethics Ahklak. Like the one at Miftahul Huda Islamic Boarding School, this cottage is one of the classic Islamic boarding schools with a salafiyah background located in Malang, East Java. The cottage is used as a location for fostering and guiding students. Apart from guiding students, the teachings of Sufism (Tarekat) are also an important element in empowering students. This study aims to provide a reflection of the practice of the tarekat as moral learning for Miftahul Huda Islamic Boarding School students. The approach in this research uses a qualitative descriptive approach. To be able to obtain accurate information, the researchers used interview, observation and documentation methods. Other than that, To be able to analyze the information that has been generated through information collection procedures, researchers use information reduction, after which the information is explained and presented. The results of the research that the author has done at the Miftahul Huda Islamic Boarding School in Malang, about the practice of the tarekat as a moral learning strategy in the modern era. It is not enough just for information, but also as a treasure and construction of modern Islamic civilization education buildings, especially in the field of Sufism.